Nilai Nutrien Rumput Lapangan dan Daun Gamal dengan beberapa Formula Urea Gula Lontar Blok - Agustinus Semang; Agustinus Paga; Aholiab Aoetpah; Lilo Jogbeth Merry Christna Kale Lado (Partner, 2013)
Nutrient Values Of Native Grass And Gliricidia Leafs With Several Blocks Of Sugar Palm Urea. A study, conducted by applying Completely Randomized Design, has been conducted to analyze nutrient content of native grass, Gliricidia leafs and urea which was mixed with palm sugar. The study took place in the Laboratory of Nutrient and Feed of Almira, Kupang from July to December 2009. Feedstuff consist of native grass forage, Gliricidia leafs, sugar palm 35%, corn meal 18%, rice bran 32%, urea 2%, salt 5%, mineral 3% and lime 5%. Observed variables consist of proximate analyses (dry matter, crude protein, crude fiber, fat, ash, free Nitrogen extract matter, Calcium and Phosphor). The results show that the nutrient values of all ration formula treatments are not significantly differ (P<0.05). It can be concluded that all nutrient content of all five ration formulations are similar.Key words: Native grass, Gliricidia leafs, Block Sugar Palm Urea, Nutrient